1954
DOI: 10.1079/bjn19540050
|View full text |Cite
|
Sign up to set email alerts
|

Food Waste and Loss of Weight in Cooking

Abstract: There is a dearth of information on the percentage of waste during preparation of food by the average woman. Such figures would be of value in dietary surveys, since some food tables give analyses for raw foods only 'as purchased', so that edible portions on dietary records must often be converted to 'as purchased' amounts before conversion to calories and nutrients.During two long-term dietary investigations, records of wastage in food preparation were made and results are presented for comparison with existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Shopping and domestic food storage habits are directly related. Some studies have shown that inappropriate food storage practices lead to the decay of both perishable and durable food (Chappell, 1954;Quested et al, 2013;Masson et al, 2017). In the case of perishable food, it is the unpleasant smell that draws the consumer's attention to the process of decay, while durable food is usually detected during 'spring cleaning'.…”
Section: Conative Componentsmentioning
confidence: 99%
“…Shopping and domestic food storage habits are directly related. Some studies have shown that inappropriate food storage practices lead to the decay of both perishable and durable food (Chappell, 1954;Quested et al, 2013;Masson et al, 2017). In the case of perishable food, it is the unpleasant smell that draws the consumer's attention to the process of decay, while durable food is usually detected during 'spring cleaning'.…”
Section: Conative Componentsmentioning
confidence: 99%